Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Algebra Esp 2

# Algebra Esp 2

Ratings: (0)|Views: 88|Likes:

### Availability:

See more
See less

08/31/2013

pdf

text

original

PÁGINA 35
EJERCICIOS DE LA UNIDADSuma y resta de enteros
1
Calcula:a)5 – 3 – 7 + 1 + 8b) 2 – 3 + 4 + 1 – 8 + 2c) 1 – 3 + 5 – 7 + 9 – 11d) 2 + 4 – 6 – 8 + 10 – 12 + 14
a) 5 – 3 – 7 + 1 + 8 = (5 + 1 + 8) – (3 + 7) = 14 – 10 = 4b) 2 – 3 + 4 + 1 – 8 + 2 = (2 + 4 + 1 + 2) – (3 + 8) = 9 – 11 = –2c) 1 – 3 + 5 – 7 + 9 – 11 = (1 + 5 + 9) – (3 + 7 + 11) = 15 – 21 = –6d) 2 + 4 – 6 – 8 + 10 – 12 + 14 = (2 + 4 + 10 + 14) – (6 + 8 + 12) = 30 – 26 = 4
2
Quita paréntesis:a)
+ (
+
)b)
– (
+
)c)
+ (
)d)
– (
)
a)
+ (
+
) =
+
+
b)
– (
+
) =
c)
+ (
) =
+
d)
– (
) =
+
3
Quita paréntesis y después opera:a) 1 (7 2 10) (3 8)b) (8 4 3) (5 8 1)c) (3 5) – (1 4) + (5 8)d) 3 (5 8) (11 4) + (13 9)
a) 1 – (7 – 2 – 10) – (3 – 8) = 1 – 7 + 2 + 10 – 3 + 8 = (1 + 2 + 10 + 8) – (3 + 7) == 21 – 10 = 11b) (8 – 4 – 3) – (5 – 8 – 1) = 8 – 4 – 3 – 5 + 8 + 1 = (8 + 8 + 1) – (4 + 3 + 5) == 17 – 12 = 5c) (3 – 5) – (1 – 4) + (5 – 8) = 3 – 5 – 1 + 4 + 5 – 8 = (3 + 4 + 5) – (5 + 1 + 8) == 12 – 14 = –2d) 3 – (5 – 8) – (11 – 4) + (13 – 9) = 3 – 5 + 8 – 11 + 4 + 13 – 9 == (3 + 8 + 4 + 13) – (5 + 11 + 9) = 28 – 25 = 3
Pág. 1
SOLUCIONES A LOS EJERCICIOSDE LA UNIDAD
1

Pág. 2
4
Calcula operando primero dentro de los paréntesis:a) (2 – 6 – 3) + (5 – 3 – 1) – (2 – 4 – 6)b) (8 – 11 – 5) – (12 – 13) + (11 + 4)c) 15 + (6 – 18 + 11) – (7 + 15 – 19) + (1 – 3 – 6)
a) (2 – 6 – 3) + (5 – 3 – 1) – (2 – 4 – 6) = (–7) + (1) – (– 8) = –7 + 1 + 8 = 2b) (8 – 11 – 5) – (12 – 13) + (11 + 4) = (– 8) – (–1) + (15) = –8 + 1 + 15 = 8c) 15 + (6 – 18 + 11) – (7 + 15 – 19) + (1 – 3 – 6) = 15 + (–1) – (3) + (– 8) == 15 – 1 – 3 – 8 = 3
5
Quita paréntesis y calcula:a) 3 – [(5 – 8) – (3 – 6)]b) 1 – (3 – [4 – (1 – 3)])c) (2 + 7) – (5 – [6 – (10 – 4)])
a) 3 – [(5 – 8) – (3 – 6)] = 3 – [(–3) – (–3)] = 3 – [–3 + 3] = 3b) 1 – (3 – [4 – (1 – 3)]) = 1 – (3 – [4 – (–2)]) = 1 – (3 – 6) = 1 + 3 = 4c) (2 + 7) – (5 – [6 – (10 – 4)]) = 9 – (5 – [6 – 6]) = 9 – 5 = 4
6
Calcula:a) (7) · (+11)b) (6) · (8)b) (+5) · (+7) · (1)d) (2) · (3) · (4)
a) (7) · (+11) = 77b) (6) · (8) = 48c) (+5) · (+7) · (1) = 35d) (2) · (3) · (4) = 24
7
Opera:a) (45) : (+3)b) (+85) : (+17)b) (+36) : (12)d) (85) : (5)
a) (45) : (+3) = 15b) (+85) : (+17) = 5c) (+36) : (12) = 3d) (85) : (5) = 17
8
Opera las expresiones siguientes:a) (+400) : (40) : (5)b) (+400) : [(40) : (5)]c) (+7) · (20) : (+10)d) (+7) · [(20) : (+10)]e) (+300) : (+30) · (2)f) (+300) : [(+30) · (2)]
SOLUCIONES A LOS EJERCICIOSDE LA UNIDAD
1

a) (+400) : (–40) : (–5) = (–10) : (–5) = 2b) (+400) : [(–40) : (–5)] = (+400) : (+8) = 50c) (+7) · (–20) : (+10) = –140 : 10 = –14d) (+7) · [(–20) : (+10)] = 7 · (–2) = –14e) (+300) : (+30) · (–2) = 10 · (–2) = –20f ) (+300) : [(+30) · (–2)] = 300 : (–60) = –5
9
Calcula:a)6 · 4 – 5 · 6 – 2 · 3b) 15 – 6 · 3 + 2 · 5 – 4 · 3c) 5 · (–4) + (–2) · 4 – 6 · (–5) – 3 · (–6)d) 18 – 3 · 5 + 5 · (–4) – 3 · (–2)
a) 6 · 4 – 5 · 6 – 2 · 3 = 24 – 30 – 6 = –12b) 15 – 6 · 3 + 2 · 5 – 4 · 3 = 15 – 18 + 10 – 12 = –5c) 5 · (–4) + (–2) · 4 – 6 · (–5) – 3 · (–6) = –20 – 8 + 30 + 18 = 20d) 18 – 3 · 5 + 5 · (–4) – 3 · (–2) = 18 – 15 – 20 + 6 = –11
10
Opera estas expresiones:a)(–5) · (8 – 13)b) (2 + 3 – 6) · (–2)c) (+4) · (1 – 9 + 2) : (–3)d) (–12 – 10) : (–2 – 6 – 3)
a) (–5) · (8 – 13) = (–5) · (–5) = 25b) (2 + 3 – 6) · (–2) = (–1) · (–2) = 2c) (+4) · (1 – 9 + 2) : (–3) = 4 · (–6) : (–3) = (–24) : (–3) = 8d) (–12 – 10) : (–2 – 6 – 3) = (–22) : (–11) = 2
11
Calcula:a)13 – [8 – (6 – 3) – 4 · 3] : (–7)b) 5 · (8 – 3) – 4 · (2 – 7) – 5 · (1 – 6)c) 12 · (12 – 14) – 8 · (16 – 11) – 4 · (5 – 17)
Pág. 3
SOLUCIONES A LOS EJERCICIOSDE LA UNIDAD